2020
DOI: 10.1007/s10803-020-04703-0
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Physical and Phenotypic Characteristics of Bangladeshi Children with Autism Spectrum Disorder

Abstract: This study explored the physical and clinical phenotype of Bangladeshi children with autism spectrum disorder (ASD). A total 283 (68 females) children were referred for screening. Assessments were conducted using a semi-structured clinical interview along with the Autism Diagnostic Observation Schedule, Second Edition (ADOS-2). Overall, 209 (45 females) children reached the ADOS-2 algorithmic cutoff for ASD. A trend for greater weight and head circumference was observed in children with ASD versus non-ASD. Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
3
1
Order By: Relevance
“…Pham et al ( 2020 ) similarly found lower BMIs among children on the spectrum with taste aversions. Other studies examining the link between autism‐linked traits as measured by the ADOS and obesity however have either not found a relationship with weight (Hill et al, 2015 ; Zuckerman et al, 2014 ) or contrary to our findings found autistic traits were associated with greater obesity (Rahaman et al, 2021 ). These contradictory results suggest that previously identified associations between obesity and autistic traits may be mediated by sample specific differences in sensory sensitivities which influence dietary intakes or other factors such as the use of medications associated with weight gain as a side effect.…”
Section: Discussioncontrasting
confidence: 99%
“…Pham et al ( 2020 ) similarly found lower BMIs among children on the spectrum with taste aversions. Other studies examining the link between autism‐linked traits as measured by the ADOS and obesity however have either not found a relationship with weight (Hill et al, 2015 ; Zuckerman et al, 2014 ) or contrary to our findings found autistic traits were associated with greater obesity (Rahaman et al, 2021 ). These contradictory results suggest that previously identified associations between obesity and autistic traits may be mediated by sample specific differences in sensory sensitivities which influence dietary intakes or other factors such as the use of medications associated with weight gain as a side effect.…”
Section: Discussioncontrasting
confidence: 99%
“…Any disruption in the steps of cortical expansion can result in abnormalities such as microcephaly or macrocephaly. [ 21 ] Rahaman et al [ 22 ] identified a trend toward increased HC in Bangladeshi children with ASD, while men with ASD exhibited significantly larger HC than men without ASD. Individuals with larger HC tended to have more severe ASD core characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In a well-characterized NDD cohort, a gold-standard observational assessment tool ADOS-2 confirmed 73.85% (209/283) as ASD cases and the remaining 26.15% (74/283) as broader NDD cases ( Rahaman et al, 2020 ). Here, the diagnosis of NDDs was mostly carried out by observing the clinical conditions of the patients and using psychological assessment tools (DSM-IV and ADOS/ADOS2) ( Rahaman et al, 2020 ). Due to the overlapping and complex clinical presentation of NDDs, it is difficult to confirm NDD diagnosis by psychological assessment.…”
Section: Introductionmentioning
confidence: 97%
“…In Bangladesh, child mental health is considered a significant health problem, with around 5 million Bangladeshi children and adolescents having psychiatric disorders (Mullick and Goodman, 2005). In a well-characterized NDD cohort, a gold-standard observational assessment tool ADOS-2 confirmed 73.85% (209/ 283) as ASD cases and the remaining 26.15% (74/283) as broader NDD cases (Rahaman et al, 2020). Here, the diagnosis of NDDs was mostly carried out by observing the clinical conditions of the patients and using psychological assessment tools (DSM-IV and ADOS/ADOS2) (Rahaman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%